2017
DOI: 10.1002/hon.2425
|View full text |Cite
|
Sign up to set email alerts
|

Nonpegylated liposomal doxorubicin combination regimen in patients with diffuse large B‐cell lymphoma and cardiac comorbidity. Results of the HEART01 phase II trial conducted by the Fondazione Italiana Linfomi

Abstract: The purpose of this phase 2, multicenter study was to determine the activity and safety of nonpegylated liposomal doxorubicin as part of "R-COMP" combination in patients with diffuse large B-cell lymphoma and coexisting cardiac disorders. The study was conducted using a Bayesian continuing assessment method using complete remission rate and rate of cardiac events as study endpoints. Between November 2009 and October 2011, 50 evaluable patients were enrolled (median age, 76 years). Median baseline left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…In a series of 530 newly diagnosed DLBCL patients ≥80 years of age, OS was prolonged in those receiving b85%, compared with ≥85%, anthracycline dose intensity [51]. Other approaches with anthracycline utilization include reduced dose intensity and use of nonpegylated liposomal doxorubicin [52][53][54][55]. Unfortunately, anthracycline dose intensity data were not available in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 530 newly diagnosed DLBCL patients ≥80 years of age, OS was prolonged in those receiving b85%, compared with ≥85%, anthracycline dose intensity [51]. Other approaches with anthracycline utilization include reduced dose intensity and use of nonpegylated liposomal doxorubicin [52][53][54][55]. Unfortunately, anthracycline dose intensity data were not available in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cardiac failure may require concepts free from or with lower doses of doxorubicin. For example, the HEART 01 phase II trial reported that a non-PEGylated liposomal doxorubicin combination regimen in patients with DLBCL and cardiac comorbidity was feasible and resulted in a 72% overall response rate, and was similar to the results seen in healthy patients receiving non-PEGylated doxorubicin (Luminari et al, 2018). For patients with dementia, and severe psychiatric comorbidities, treatments may not always be possible to deliver due to poor compliance, and treating the malignant disease may be of lower priority.…”
Section: Comorbidities and Novel Targeted Treatments And Other Treatmmentioning
confidence: 92%
“…grade 3-4 cardiac adverse events were observed in 6 patients. no significant deterioration of lVeF was identified in any of the subjects [10].…”
Section: Review Of Relevant Literaturementioning
confidence: 70%